ANALISIS YURIDIS HUBUNGAN PEMERINTAH DAERAH DAN DEWAN PERWAKILAN RAKYAT DAERAH MENURUT UU NOMOR 23 TAHUN 2014 - Sugianto, Bambang (Solusi, 2017)
The purpose of this study is to explain and analyze the relationship of local government and regional representatives Deawan. This research uses normative juridical method. Results of research In carrying out its duties and functions despite the equal position between the Regional Government and the DPRD. Supervision remains in place as the duties of the DPRD always exercise good oversight of the government in running the wheels of the government and include supervision of the use of APBD and Regional Policies. The working relationship of Local Government with DPRD according to Law Number 23 Year 2014 on Regional Government, namely:1.Relationship in the making of Regional policy, 2. Discussion and Ratification of Regional Regulations, 3. Relationship in the discussion of Regional Expenditure Budget Plan (RAPBD), 4. Relationship in the field of personnel, 5.Hubungan In the Policy on the management of Regional Goods, 6. Relations in the field of Policy and political supervision of the region.